2020
DOI: 10.3389/fpsyg.2020.01505
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Relational Embeddedness, Absorptive Capacity, and Learning Orientation on SMEs’ Competitive Advantage

Abstract: The combination of external new knowledge and organizational capability has become a cornerstone in the internationalized enterprises. Sources of knowledge acquisition are among the most valuable resources that an internationalized firm can achieve competitive advantage. This study aims to explore this phenomenon between knowledge sources and competitive advantage in the context of internationalized small and medium enterprises (SMEs) mainly by a quantitative approach. Based on contextual nature of resource–ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
27
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 86 publications
(196 reference statements)
0
27
1
Order By: Relevance
“…In conclusion, external knowledge is acquired, converted and utilized by internationalized enterprises based on RE (Alinaghian et al, 2020). External and internal knowledge can be combined, and international exploration can be strengthened in the process of organizational learning (García-Villaverde et al, 2018; Wu et al, 2020). Therefore, here is the following hypothesis made in the study: H3: Relational embeddedness positively correlates with international exploration.…”
Section: Relational Embeddedness (Re)mentioning
confidence: 83%
See 4 more Smart Citations
“…In conclusion, external knowledge is acquired, converted and utilized by internationalized enterprises based on RE (Alinaghian et al, 2020). External and internal knowledge can be combined, and international exploration can be strengthened in the process of organizational learning (García-Villaverde et al, 2018; Wu et al, 2020). Therefore, here is the following hypothesis made in the study: H3: Relational embeddedness positively correlates with international exploration.…”
Section: Relational Embeddedness (Re)mentioning
confidence: 83%
“…al., 2018;Wu et al, 2020). Moreover, following and extending prior organizational learning studies, the current study provides an integrated theoretical model which has not yet been identified or verified in the literature.…”
mentioning
confidence: 77%
See 3 more Smart Citations